Mirza Bukhari: The Journey from Entrepreneurship to Collecting - Jannat Ismailova (International Journal on Integrated Education, 2021)
The article highlights the contribution of collectors to the formation of museum collections. In particular, the work of Mirza Bukhari, a local collector of ancient artefacts in Samarkand, his travels in Russian cities and his contribution to the formation of Central Asian collections in foreign museums is analysed on the basis of sources.